Dinamika Pembaruan Pendidikan Islam di Indonesia Tahun 1908-2024 (Dalam Aspek Pengelolaan dan Pengembangan Peserta Didik) - Rizqi, Ahmad Ainur (Madrasah Ibtidaiyah Education Journal, 2024)
Educational institutions in Indonesia have a long history, starting from before the independence of the Indonesian State, namely during the Dutch colonial period and the Japanese colonization, this study uses the library research methodology, so that in collecting the data can be interpreted using a qualitative research approach. Islamic education in Indonesia began during the colonial period by using a learning system in surau, mosques, and “pondok pesantren”, this education system is still traditional and has not been systematized as it is now. The renewal of Islamic Education in Indonesia began when the Dutch established formal schools which at that time the students were still mostly from the nobility and the rich, then several Islamic institutions established Islamic religious-based schools and received challenges and even rejection from the Dutch government, during the Dutch colonial period the renewal of Islamic Education in Indonesia began to be noticed by the Japanese government until then Indonesia Merdeka Islamic Education was fully considered by the government until 2024, although there were many curriculum changes but Islamic Education still received special attention by the Indonesian government.